2021
DOI: 10.1038/s41598-021-93588-9
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among patients with sepsis associated with a bispectral electroencephalography (BSEEG) score

Abstract: We have previously developed a bispectral electroencephalography (BSEEG) device, which was shown to be effective in detecting delirium and predicting patient outcomes. In this study we aimed to apply the BSEEG approach for a sepsis. This was a retrospective cohort study conducted at a single center. Sepsis-positive cases were identified based on retrospective chart review. EEG raw data and calculated BSEEG scores were obtained in the previous studies. The relationship between BSEEG scores and sepsis was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…All-cause mortality among the study participants were gathered from a review of medical records and obituary records as previously reported ( 26, 27, 29, 30, 34 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All-cause mortality among the study participants were gathered from a review of medical records and obituary records as previously reported ( 26, 27, 29, 30, 34 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our previously published work describes the details of study subjects and recruitment procedures (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Briefly, we identified eligible subjects 18 years old or older from patients at UIHC either admitted as inpatients or visiting the emergency room.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative increases in delta and theta power and reduced spectral peak frequencies were found in septic patients [51][52][53][54]. Increased slowing was associated with poor outcomes, including delirium [54] and death [55]. In animal models, increased wake delta power [56], slowed EEG [57], and reduced theta frequencies have been described [26].…”
Section: Discussionmentioning
confidence: 99%
“…Increased delta and theta power, with high inter-individual variability, as well as a general slowing of oscillatory activity in the REM-like state under urethane is in line with slowing of EEG activity during awake, or wake-like states, described in sepsis patients (Götz et al, 2016; Rosengarten et al, 2012; Straver et al, 1998; Urdanibia-Centelles et al, 2021). Increased slowing was associated with poor outcomes, including delirium (Urdanibia-Centelles et al, 2021) and death (Yamanashi et al, 2021). In animal models, increased wake delta power (Kafa et al, 2010), slowed EEG (Kurita et al, 2010), and reduced theta frequencies have been described (Mamad et al, 2018).…”
Section: Discussionmentioning
confidence: 99%